Influence of artificial intelligence on the legal system - Martsenko, Nataliia (Studia Prawnoustrojowe, 2021)
Due to the extremely rapid development of technologies and artificial intelligence, there are changes in civil law relations and their legal regulation. Lawyers and legislators are trying to solve the new problems facing the legal system by using classical approaches in legal regulation. However, such decisions are not always effective. On the one hand, lawyers seek to regulate in detail the mechanism of creation and use of artificial intelligence. On the other hand, the state contributes to their development intending to win the world race for the most advanced technologies. The problem is also what place the artificial intelligence in law should occupy. Is it an object or subject of law (person, an entity)? These issues are philosophical and need deep research. The author offers his thoughts on the solution to this issue. This article explores the features of the interaction between law and artificial intelligence, the legal regime of artificial intelligence, and the risks that arise when addressing the place of artificial intelligence in law.According to the authors, the law should find appropriate practical ways to build the digital world. It does not have to be specific rules of conduct. Artificial intelligence laws can be abstract enough, but as effective as possible. Artificial intelligence must be used to enhance human dignity, and not to eliminate it.